Bridging gaps in medical field - New Straits Times, (2012)
ATEAM of medical students from AIMST . University, University of Malaya and Universiti Sains Malaysia collaborated to create history by organising the inaugural National Medical Student's Convention 2012. With the mission of bridging knowledge of medicine and entrepreneurship, the convention saw eminent doctors from various fields of medicine and successful entrepreneurs sharing their knowledge.